2011
DOI: 10.1179/026708309x12506933873387
|View full text |Cite
|
Sign up to set email alerts
|

Hot ductility of TWIP steels

Abstract: The hot ductility of twin induced plasticity (TWIP), 0·6 wt-C steels containing 18–22 wt-Mn with N levels in the range 0·005–0·023 wt- and the Al additions either low (<0·05 wt-) or high (1·5 wt-) has been examined. Little change in ductility occurred in the temperature range 1100–650°C as the structure was always fully austenitic. Ductility was generally poor (<40), reduction of area values, the best ductility at the higher Al level being given by the steel with the lowest N and S levels. Because the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
77
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(82 citation statements)
references
References 117 publications
(473 reference statements)
3
77
0
Order By: Relevance
“…The cooling rate in previous work [3,5,8] after reheating has generally been 60 o C/min, which is higher than the recommended cooling rate of ≤25 o C/min needed to coarsen the TiN particles to obtain the maximum ductility or to give the maximum segregation for B to strengthen the grain boundaries [13]. In this exercise two cooling rates, 12 o C/min min and 60 o C/min have been examined.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The cooling rate in previous work [3,5,8] after reheating has generally been 60 o C/min, which is higher than the recommended cooling rate of ≤25 o C/min needed to coarsen the TiN particles to obtain the maximum ductility or to give the maximum segregation for B to strengthen the grain boundaries [13]. In this exercise two cooling rates, 12 o C/min min and 60 o C/min have been examined.…”
mentioning
confidence: 99%
“…Previous work [3,5,7] has concentrated on the simpler high Al, TWIP steels giving a room temperature yield strength of 800MPa. However, if a higher strength level is required ~1000MPa, then Nb needs to be added [8].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…20Mn in present work should be ascribed to the larger amount of AlN inclusions and less addition of Mn solute [16]. The AlN impurity is mainly produced by the higher N content in steel making, and prefers to distribute along the rolling direction during the hot rolling process.…”
Section: Matec Web Of Conferencesmentioning
confidence: 65%
“…Actually, few work has been done about the study of the hot ductility behavior of TWIP steels [21][22][23][24][25][26][27][28], taking into account various experimental parameters, where the most significant is the microstructural conditioning before tensile testing. Generally, the results of these research works have shown a decrease of the hot ductility in the temperature range of 700-1000°C due to the AlN precipitation and the high Mn content (i.e.…”
Section: Introductionmentioning
confidence: 99%